Arctic sea ice and atmospheric circulation under the GeoMIP G1 scenario. Issue 2 (29th January 2014) - Moore, John C.; Rinke, Annette; Yu, Xiaoyong; Ji, Duoying; Cui, Xuefeng; Li, Yan; Alterskjær, Kari; Kristjánsson, Jón Egill; Muri, Helene; Boucher, Olivier; Huneeus, Nicolas; Kravitz, Ben; et al.
Abstract We analyze simulated sea ice changes in eight different Earth System Models that have conducted experiment G1 of the Geoengineering Model Intercomparison Project (GeoMIP). The simulated response of balancing abrupt quadrupling of CO2 (abrupt4xCO2) with reduced shortwave radiation successfully moderates annually averaged Arctic temperature rise to about 1°C, with modest changes in seasonal sea ice cycle compared with the preindustrial control simulations (piControl). Changes in summer and autumn sea ice extent are spatially correlated with temperature patterns but much less in winter and spring seasons. However, there are changes of ±20% in sea ice concentration in all seasons, and these will induce changes in atmospheric circulation patterns. In summer and autumn, the models consistently simulate less sea ice relative to preindustrial simulations in the Beaufort, Chukchi, East Siberian, and Laptev Seas, and some models show increased sea ice in the Barents/Kara Seas region. Sea ice extent increases in the Greenland Sea, particularly in winter and spring and is to some extent associated with changed sea ice drift. Decreased sea ice cover in winter and spring in the Barents Sea is associated with increased cyclonic activity entering this area under G1. In comparison, the abrupt4xCO2 experiment shows almost total sea ice loss in September and strong correlation with regional temperatures in all seasons consistent with open ocean conditions. The tropospheric circulation displays a Pacific North America pattern‐like anomaly with negative phase in G1‐piControl and positive phase under abrupt4xCO2‐piControl.